RISE OF THE AUSTRALIAN NEUROHUMANITIES conversations between neurocognitive research and Australian literature. - Vernay, Jean-François ([S.l.] : ROUTLEDGE, 2021)
This exciting one-of-a-kind volume brings together new contributions by geographically diverse authors who range from early career researchers to well-established scholars in the field. It unprecedentedly showcases a wide variety of the latest research at the intersection of Australian literary studies and cognitive literary studies in a single volume. It takesAustralian fiction on the leading edge by paving the way for a new direction in Australian literary criticism.
OCLC-licensed vendor bibliographic record.
Keywords: LITERARY CRITICISM / Australian & Oceanian; Australian fiction -- 20th century -- Psychological aspects; Australian fiction -- 21st century -- Psychological aspects; Philosophy of mind in literature; Creativity in literature